International Management Strategy: An Empirical Study (Global Journal of Management and Business Research, 2014)
In multinational firms, strategies are initiated at the corporate/headquarter level and the subsidiary level. Each of the two levels of strategy has an important and distinct role to play in achieving and sustaining competitive advantage, although key elements of the multinational firm strategy are formulated at the corporate level, strategies dealing with the implementation of the strategy are typically done at the subsidiary level. The multinational firm has to strike a balance between having a single global strategy, such as a single website for the whole company, or have mini-replicas around the world, each developing its subsidiary strategy. After reading this paper you should be able to identify and describe levels of global strategy; identify and describe subsidiaries strategic roles; discuss the advantages and disadvantages of the different subsidiary roles; identify and discuss the generic strategies.